STRATEGI KOMUNIKASI UNTUK MENGATASI MASALAH KOMUNIKASI KETIKA BERKOMUNIKASI DENGAN NATIVE SPEAKER BAHASA JEPANG (Studi Kasus pada Mahasiswa Tingkat III Program Studi Pendidikan Bahasa Jepang FKIP Universitas Riau) - Setiawati, Sulis; Rahayu, Nana; Aibonotika, Arza (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
Abstract: This research aims to find outthe communication strategies which Japanese learner’s use in face-to-face interactions with native speaker of Japanese. This research also aims to find out how native speaker to respond communication strategies use by the Japanese learner’s. The research objects were fifteen of Japanese education study program students in the sixth semester at University of Riau. This research used qualitative and analytical approach combined with quantitative analysis to count the frequency of communication strategies employed by the students. Research data (visual) were collected by recording the interview by students and native speaker.The latest taxonomy of communication strategies designed by Dörnyei (1995) were used to analyze the data. The result showed that students use three three types of communication strategies, namely achievement strategies, stalling or time-gaining strategies, and topic avoidance strategies. This research could be the basis for futher studies involving more subjects to ensure the generalizability of the results.Key Words: communication strategies, Japanese learner, achievement strategies